Localised plasmacytoma presenting as right chest wall swelling - Goel, Mahak; Siddiqui, Azaz Akhtar; N. V., Skanda; Kumar, Vivek (International Surgery Journal, 2023)
Development of any swelling in the right lower chest wall or right upper abdomen is an unusual presentation. Hence the localisation of the origin of swelling becomes difficult to ascertain through clinical examination alone. Accurate diagnosis requires detailed investigation and ruling out of differentials one by one. We would like to share one such case of a patient presenting to surgery OPD with complaint of swelling in the lateral aspect of right chest wall which on investigations turned out to be a rib tumour arising from the bone marrow. Lady of age 57 years presented to us with h/o swelling in lateral aspect of right chest wall which gradually increased in size over 3 years and associated with pain for last 5 months. On exam an oval swelling of size 8×5 cm seen in lateral wall of right lower chest wall. On detailed investigations, the swelling was diagnosed as a plasma cell tumour of right 8th rib. Any chest wall or abdominal swelling needs detailed evaluation before proceeding for surgical intervention. It is important to keep various differential diagnosis in mind considering clinical factors and site of swelling to make an accurate diagnosis.